Penerapan Prinsip Pasar Modal Syariah yang Terindeks Di Lebaga Otoritas Jasa Keuangan Indonesia - Muhammad Isa; Bunga Sari (INSTITUT AGAMA ISLAM TAZKIA, 2020)
This research has purposes to analysts the implementation of Financial ServiceAuthority Regulation No.15/POJK.05/2015 About Applying Sharia Orientation in StockMarket. Another purpose is to found positive effects of applying its rule.This research is using qualitative method with descriptive approach and takes twomonths to do the research. This research uses Financial Service Authority RegulationNo.15/POJK.05/2015 About Applying Sharia Orientation in Stock Market along withother supporting regulations as samples. This research has the result that the samples arein line with the orientation of sharia in Islam, but on the other hand there are still someobstacles in some aspects of the overall application.